2022
DOI: 10.22190/fupes220216005s
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Jump Performance, Speed and Cod Speed in Elite Female Soccer Players

Abstract: The purpose of this study was to present the physical performance of elite female soccer players and to analyze the relationship between jump performance, speed and COD ability. Sixteen elite female soccer players (age: 20.05±2.85; height: 166.47±4.83cm; body weight: 60.52±8.30kg, BMI 21.88±2.86) from a women's club who played the highest rank of the competition took part in this study. The jump, speed and COD abilities of each player were determined using: (1) the Squat jump (SJ), (2) Countermovement Jump (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…This finding provides mixed support for previous studies assessing the relationship between jump height from SJ and subsequent athletic performance. The current finding complements an existing body of literature which found no association between SJ jump height and various training and competition performance outcomes in elite karate (Loturco et al, 2014), basketball (Pojskic et al, 2018), surfing , soccer (Gonçalves et al, 2021;Saidi et al, 2020;Saidi et al, 2022;Saidi et al, 2019;Stanković et al, 2022), cross-country skiing (Carlsson et al, 2012), and track and field (Loturco et al, 2019) athletes.…”
Section: Squat Jumpsupporting
confidence: 83%
“…This finding provides mixed support for previous studies assessing the relationship between jump height from SJ and subsequent athletic performance. The current finding complements an existing body of literature which found no association between SJ jump height and various training and competition performance outcomes in elite karate (Loturco et al, 2014), basketball (Pojskic et al, 2018), surfing , soccer (Gonçalves et al, 2021;Saidi et al, 2020;Saidi et al, 2022;Saidi et al, 2019;Stanković et al, 2022), cross-country skiing (Carlsson et al, 2012), and track and field (Loturco et al, 2019) athletes.…”
Section: Squat Jumpsupporting
confidence: 83%
“…In the present study, significant relationships were found between COD180 and 10-m (r=0.53 to 0.70) and 30-40-m (r=0.51 to 0.65). In the same line, a recent study showed large correlations between 10-m speed and COD (Pro Agility test/5-10-5 r=0.59; Zig-Zag test r=0.55) [39]. On the other hand, Lockie et al [3] found heterogeneous results in collegiate women's soccer players.…”
Section: Discussionmentioning
confidence: 88%
“…In the present study, significant relationships were found between COD180 and 10 m (r = 0.53 to 0.70) and 30-40 m (r = 0.51 to 0.65). In the same line, a recent study showed large correlations between 10 m speed and COD (Pro Agility test/5-10-5 r = 0.59; Zig-Zag test r = 0.55) [39]. In contrast, Lockie et al [3] found heterogeneous results in collegiate women's soccer players.…”
Section: Discussionmentioning
confidence: 91%
“…However, studies analysing the relationship between COD tests and 30 m time have been found. One study showed large correlations between 30 m speed and COD (Pro Agility test/5-10-5 r = 0.66; Zig-Zag test r = 0.55; 9-6-3-6-9 test r = 0.58) in elite female soccer players [39]. Another study analysed male soccer players and found a large correlation between linear speed (30 m) and the Zig-Zag test (r = 0.56-0.60) [40,41].…”
Section: Discussionmentioning
confidence: 99%